Cost of credit and interest rate caps in a COVID-19 pandemic Will the lower-income sectors be favored with this measure? - Ballesteros, Ana (2021)
For some years now, the government, mainly from the legislature, and a large part of the population have questioned the application of high interest rates to credits granted to lower-income sectors; considering measures such as the cap on interest rates to curb these high rates called usury and charged by financial institutions. The application of measures like this is not a new economic recipe, since many developed and developing countries - such as Peru - carried it out with mostly disastrous results and to the detriment of the sectors that were precisely intended. to attend. In this sense, the theory of the credit market is exposed, the same that in conditions of perfect competition determines the market interest rate. In other words, applying limits to these rates only lead to credit contraction, harming and excluding from the financial system the lower-income sectors, considered those with the highest credit risk. Finally, alternative measures are presented that can lead to the objective of providing the most vulnerable sectors with better interest rates and contributing to their growth. Finally, a good example of interest rate reduction is presented, particularly in a situation of financial and economic crisis with the measure applied by the government and the Central Reserve Bank of Peru -Reactiva Perú-, which allowed the lower income sectors income to enjoy low interest rates at levels never seen before.